Study of structural and optical properties of CaMoO4 nanoparticles synthesized by the microwave-assisted solvothermal method - Botelho, G. (2016)
Calcium molybdate (CaMoO4) nanoparticles were synthesized by using a rapid assisted-microwave solvothermal method. X-ray diffraction measurements, Fourier transform Raman and Fourier transform infrared spectroscopies, revealed that the samples all have a scheelite-type tetragonal structure. In addition, the data obtained from the Rietveld refinements revealed distortions of the [Ca[sbnd]O] and [Mo[sbnd]O] bonds that led, in turn, to distortions of the [CaO8] and [MoO4] clusters. The presence of irregular spherical-like CaMoO4 nanoparticles and the corresponding crystallographic arrangement were confirmed and determined via transmission electron microscopy and high resolution transmission electron microscopy, respectively. First-principles quantum mechanical calculations based on the density functional theory at the B3LYP level were employed in order to understand the band structure and density of states of CaMoO4 in the excited singlet and triplet states. Furthermore, the optical properties were investigated by performing ultraviolet–visible spectroscopy and photoluminescence (PL) measurements. Maximum PL emission of CaMoO4 powders was detected in the green-region wavelength of the electromagnetic spectrum; this emission was attributed to the distorted [MoO4] clusters.